The Effect of Product Innovation, Price, and Service Quality on Purchasing Decisions for Herbalife Products - Anggraini, Yulia; Putri, Nanda Meilania (Journal of Islamic Economics (JoIE), 2023)
Introduction: Purchasing decisions are individual activities and are directly involved in making decisions to purchase products offered by sellers. Consumer purchase decisions can occur if product innovation, prices and services provided are appropriate and satisfy consumers. This study aims to determine the effect of Product Innovation, Price, and Service Quality on Purchasing Decisions at Rumah Nutrition Melodina Club Dolopo Madiun. Research Methods: This study uses quantitative methods, using primary data. This study uses a census study technique, with a total sample of 62 respondents. The data analysis technique used in multiple linear regression analysis. Results: Product innovation has a positive and significant effect on purchasing decisions, Price partially has a positive and significant effect on consumer purchasing decisions, Service quality partially has a positive and significant effect on consumer purchasing decisions,  the coefficient of determination R2 (Adjusted R Square) is positive at 0.789 and the Fcount value is 76.953> Ftable value of 2.68 so product innovation, price and service quality simultaneously have a positive and significant effect on purchasing decisions    Conclusion: Based on the results of the study, it can be concluded that product innovation partially affects consumer purchasing decisions, price partially affects consumer purchasing decisions, service quality affects consumer purchasing decisions and product innovation, price and service quality simultaneously affect purchasing decisions.